Intervention of Slow Stroke Back Massage (SSBM) Therapy at the Garut For Hypertensive Elderly - Wulan Purnamasari, Indah; Wahyudi, Iwan (Nursing Case Insight Journal, 2025)
The prevalence of diseases in the elderly increases with age due to declining body functions, including blood vessel function, leading to conditions like hypertension. Hypertension, characterized by systolic blood pressure over 140 mmHg and diastolic over 90 mmHg, is a major risk factor for kidney failure, heart failure, and stroke. This case study examines nursing care with slow stroke back massage (SSBM) therapy as an intervention to reduce blood pressure in elderly hypertensive patients. A descriptive case study approach was used, involving nursing assessment, diagnosis, intervention, implementation, and evaluation. The subject was an elderly patient, Mrs. P, at the Garut Elderly Home Service Unit. The interventions, particularly slow stroke back massage, effectively addressed the patient's discomfort and sleep pattern disturbances. The risk of decreased cardiac output and falls were partially resolved. The sustained management of hypertension requires a longer timeframe for optimal control of blood pressure. Slow stroke back massage significantly impacts lowering blood pressure in patients with hypertension and is recommended as a beneficial therapy